Democracy and Fake News in the Age of Cyberspace - Mariam Mohammed; Adem Bölükbaşı (Skad)
This article attempts to evaluate the negative effects of fake news in cyberspace on democracy in today's societies, and to develop measures and suggestions for its negative consequences. For this purpose, we first discussed the social contract theory, which deals with the peaceful and secure coexistence of societies. Then, the relationship between the spread of fake news in cyberspace and the cyber security system that needs to be created against it and the social contract that needs to be rebuilt in today's societies are mentioned. It has been concluded that phenomena such as fake news, misinformation and disinformation which are increasingly common in cyberspace today, have an effect peculiar to the post-truth society and negatively affect the functioning of democracy. It can be claimed that fake news is spreading much faster and more effectively in today's societies thanks to cyber space and it misleads many people. As a result, democratic processes such as elections and election campaigns are also adversely affected. In order to combat fake news in cyber space more effectively, measures such as increasing individual responsibility awareness and cyber literacy among citizens on this issue, establishment of fact-checking programs by governments and social media platforms should be taken. Both public authorities and social media companies should fulfill their responsibilities in this regard.